A Dynamic Ellsberg Urn Experiment - Adam Dominiak; Peter Dürsch; Jean-Philippe Lefort (University of Heidelberg, Department of Economics, 2009)
Two rationality arguments are used to justify the link between conditional and unconditional preferences in decision theory: dynamic consistency and consequentialism. Dynamic consistency requires that ex ante contingent choices are respected by updated preferences. Consequentialism states that only those outcomes which are still possible can matter for updated preferences. We test the descriptive validity of these rationality arguments with a dynamic version of Ellsberg's three color experiment and find that subjects act more often in line with consequentialism than with dynamic consistency.
urn:nbn:de:bsz:16-opus-98286
Keywords: D81; C91; 330; Non expected utility preferences; ambiguity; updating; dynamic consistency; consequentialism; Entscheidung; Präferenztheorie; Test